PENGARUH TOTAL QUALITY MANAGEMENT (TQM) TERHADAP KINERJA PERUSAHAAN (STUDI PTPN V SEI PAGAR KAB. KAMPAR) - Yunita Erni Siska; Restu Restu; Siregar Andreas Prima (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of total quality management (tqm) on company performance by using three independent variables namely leadership, employee involvement, and continuous system improvement on the dependent variable, namely company performance. The population in this study were the general manager and all employees of PTPN V Sei Pagar Kab. Kampar. The sampling technique used was saturated sampling technique or census by determining the entire population in this study was 147 respondents. The data were tested using validity test, reliability test and classical assumption test. The analytical method used in this research is quantitative analysis and linear regression analysis using SPSS 23 for windows program. The results of this study indicate that 1.) leadership has a positive and significant effect on company performance, 2.) employee involvement and empowerment has a positive and significant impact on company performance, 3.) continuous system improvement has a positive and significant impact on company performance. The result of the calculation of the coefficient of determination (R2) of 0.457 means that the effect of total quality management (tqm) on the company's performance is 45.7% while the remaining 54.3% is influenced by other variables not included in this model.Keywords: Total Quality Management, Leadership, Employee Involvement, And Continuous System Improvement, Company Performance